Underlying Climate Controls in Triple Oxygen (16 O, 17 O, 18 O) and Hydrogen (1 H, 2 H) Isotopes Composition of Rainfall (Central Pyrenees) - Giménez, Reyes; Bartolomé, Miguel; Gázquez, Fernando; Iglesias, Miguel; Moreno, Ana (Frontiers in Earth Science, 2021)
Studies of rainfall isotopic composition in the Iberian Peninsula are scarce and, to date, none of them has provided analyses of the triple oxygen isotopes, preventing from the complete understanding of current atmospheric processes in this region. We investigate the rainwater d17O, d18O and dD, and derived parameters 17O-excess and d-excess, in a mountain site in the Central South Pyrenees (Villanúa, Huesca, Spain) to identify the main factors (regional and local) controlling the isotopic composition of precipitation at event scale. The samples were collected on a rainfall-event basis during two years (from July 2017 to June 2019) and meteorological variables (temperature, relative humidity - RH - and rainfall amount) were monitored at the sampling site. The d17O, d18O and dD values were higher during summer and lower during the rest of the year. In contrast, the 17O-excess and d-excess were lower during summer and higher during the remaining months. We found that the isotopic parameters are weakly correlated with rainfall amount during each event, but they strongly depend on changes in air temperature and, moderately, on RH. We consider other factors affecting the isotopic composition of rainfall events which resulted to have an important role, such as the influence of the moisture source and trajectory throughout the variations in the synoptic pattern during rainfall events. This dataset can be useful for further comprehensive atmospheric and hydrological studies, with application to paleoclimatic investigations.